Antioxidative Properties of White Saffron Extract (Curcuma mangga Val) in The 0-Carotene Bleaching and DPPH-Radical Scavenging Methods - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Study on antioxidative properties of white saffron extract in the emulsion system of b-carotene linoleic acid (b-carotene bleaching method) and DPPH-radical scavenging method was undertaken. The objective of this study was to examine the antioxidative activity of white saffron extract in the emulsion system of b-carotene linoleic acid and for radical scavenging activity by DP PH method. The extraction was carried out as follows: fresh white saffron was peeled and blanched in the 0.5% boiling citric acid solution for 5 minutes, the blanched white saffron was grated, and added distilled water. The ratio between grated white saffron and distilled water were 1 : 1